About Celebrating PPM'S 60 Years (1955-2015) - PPM, Persatuan Pustakawan Malaysia (2015)
Towards the middle of the 20th Century there was a general assumption that with the advent of technology, libraries would be rendered obsolete. Today however, despite the proliferation of technology in library applications and the metamorphosis of the traditional book-based library into the digital library, libraries and librarians have adapted well to their new environment - the Cyber World.